The Effectiveness of Insectary Plant that Attracts and Sustains Beneficial Arthropods to Control Spodoptera frugiperda J.E Smith (Lepidoptera: Noctuidae) in Maize - Dewi, Vien Sartika; Sjam, Sylvia; Sulaeha, Sulaeha; Sulastri, Elsa (Bogor Agricultural University, Indonesia, 2025)
Spodoptera frugiperda J.E. Smith, or fall armyworm (FAW), is a significant pest in maize plants and can reduce crop yields. Synthetic insecticides are still used to control S. frugiperda, but their use harms the environment and non-target organisms and can cause pests to become resistant. For this reason, alternative environmentally friendly technologies are needed, such as habitat management by planting insectary plants. This research aims to evaluate the potential of insectary plants to attract beneficial arthropods to suppress the S. frugiperda population and minimize the damage caused. This research activity was carried out using field research. The treatment in this research was the type of insectary plant used, and as a comparison, observations were made on land managed by farmers. The research results show that habitat management by planting insectary plants can increase the population of beneficial arthropods such as Coccinellidae, Formicidae, Miridae, Staphylinidae, and Araneidae. Increasing the population of beneficial arthropods can suppress the population of S. frugiperda so that its damage decreases and yields increase. These results show that planting insectary plants has the potential to prevent outbreaks of S. frugiperda, which can be combined with the application of other environmentally friendly technologies.